Sistem Pakar Untuk Mendiagnosa Anak Penderita Tuna Grahita Menggunakan Metode Certainty Factor - Mardiana, Yessi; Ninosari, Devina (Informasi Interaktif : Jurnal Informatika dan Teknologi Informasi, 2024)
The ability of expert systems to complete the various tasks that are usually done by experts to be the main attraction for the system. Expert systems have been used as tools in various areas of life. One example of an application that can be made is the Expert System disorder Tuna Grahita in children using Certainty Factor method. This method is used to see the level of interest that is growing with the existence of this expert system can allow users to be rewarded online. System using PHP Programming Language and MySQL Database. The expert system generated can help users to diagnose the type of disorder Tuna Grahita and provide solutions to the disease online. Keywords: Expert system , Certainty Factor , Tuna Grahita